Cancer Therapy: A Magnetofluorescent Carbon Dot Assembly as an Acidic H2O2‐Driven Oxygenerator to Regulate Tumor Hypoxia for Simultaneous Bimodal Imaging and Enhanced Photodynamic Therapy (Adv. Mater. 13/2018). Issue 13 (30th March 2018) - Jia, Qingyan; Ge, Jiechao; Liu, Weimin; Zheng, Xiuli; Chen, Shiqing; Wen, Yongmei; Zhang, Hongyan; Wang, Pengfei
Abstract : In article number 1706090, Jiechao Ge, Pengfei Wang, and co‐workers design and prepare magnetofluorescent Mn‐carbon dots as an acidic H2 O2 ‐driven oxygenerator to increase the oxygen concentration in hypoxic tumors for simultaneous bimodal fluorescence/T1 ‐weighted magnetic resonance imaging and enhanced photodynamic therapy. Their work explores a new biomedical use of carbon dots and provides a versatile carbon‐nanomaterial candidate for multifunctional nanotheranostic applications.